Single- and Multiple-Dose Trials to Determine the Pharmacokinetics, Safety, Tolerability, and Sex Effect of Oral Ginsenoside Compound K in Healthy Chinese Volunteers - Chen, Lulu; Zhou, Luping; Huang, Jie; Wang, Yaqin; Yang, Guoping; Tan, Zhirong; Wang, Yicheng; Zhou, Gan; Liao, Jianwei; Ouyang, Dongsheng (Frontiers in Pharmacology, 2018)
Background and objectives: Ginsenoside compound K (CK) is a candidate drug for rheumatoid arthritis therapy. The objective of this study was to investigate the pharmacokinetic properties, safety and tolerability of CK. Methods: In randomized, double-blind trials, 76 healthy Chinese subjects received 1 of 7 single oral doses (25, 50, 100, 200, 400, 600, 800 mg) of CK or placebo under fasting condition, and another 36 subjects received repeated oral doses (100, 200 or 400 mg) of CK or placebo for up to 9 days a week after a corresponding single dose, after breakfast. Both sexes were equally represented in the two trials. Pharmacokinetic parameters of CK and its metabolite 20(S)-protopanaxadiol (PPD) were calculated and statistically analyzed according to the plasma concentration data. Tolerability was evaluated by adverse events (AEs) and laboratory examinations. Results: The range of time to maximum concentration (Tmax) was 1.5-6.0 h, with a linear increase in the exposure of CK over the dose range of 100-400 mg. Steady state was reached after the 7th administration, and the accumulation index range was 2.60-2.78. Sex differences were characterized by a higher exposure in females than males with the single administration after breakfast. In addition, no severe AEs were observed. Conclusion: CK was safe and well-tolerated over the treatment period. The sex- and food-related impacts on CK pharmacokinetics need further investigations to be validated.